First lactation performance of Holstein-Friesian cows derived from sexed insemination doses - Polgár, József Péter; Nagy, Szabolcs Tamás; Abella, Dorina; Faludi, Gergely; Bene, Szabolcs (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
Nowadays, the use of sexed sperm is a part of everyday practice in cattle breeding. Among other things, this technology is responsible for the large-scale genetic progress, which enables higher and higher quality production. The paternal effect is less studied in this area, as research primarily focuses on the maternal effects on embryonic development and the phenotype of the offspring. The study’s aim was to evaluate the paternal effect on the production parameters of offspring from sexed and conventional AI doses. For this purpose, several years of reproductive and milk production data of a dairy farm characterized by a high level of milk production were used, based on which the first lactation milk production of offspring derived from sexed and normal sperm of given bulls was compared. The data were obtained from the Riska management software. To build the database, data on the production, origin and first calving age of heifers calved between 2015 and 2019 were used. Based on our results, the type of sperm used from individual bulls affects the first lactation production. In the future, it is therefore recommended to carry out studies that reveal in more detail the effect of sexing procedure on the reproductive material of bulls.